Effects of EFL vocabulary instruction on Arab learners usage of lexical collocations in speaking performance - Abu Sneida, Taghreed I.G.; Yahya, Muhammad Yasir; Husain, Salina (Universiti Putra Malaysia, 2023)
For many decades, the role of the learner's mother tongue in foreign and second language classrooms has been a topic of debate. EFL teachers may present and explain vocabulary in students native language, they may do so in the target language, or they may keep switching between the two. The aim of the current study is to investigate how EFL vocabulary instruction affects EFL Arab learners' usage of English lexical collocations in their speaking performance through implementing several working memory strategies. A quasi-experimental, mixed method design was adopted comparing teacher code-switching and L2 explanations in teaching lexical collocations. Within twenty-six sessions of teaching intervention to teach lexical collocations to EFL learners, the study measured learners' responses to vocabulary instruction in the two experimental groups. The study also explored how working memory strategies used by learners in response to vocabulary instruction may enhance learning lexical collocations by EFL learners. For this purpose, 45 Arab elementary EFL learners in the English language centre in Kuala Lumpur were divided into three groups (code-switching, L2 explanation group, and control group); they completed three speaking tests, pre, and post-test and delayed post-test. The results indicated that both the code-switching group and the L2 explanation group were improving their vocabulary; however, the study showed an important role of L1 in learning lexical collocation. The findings revealed that working memory strategies assisted learners to retain collocations effectively. The study included several pedagogical suggestions and implications for future research to improve the standard for teaching, learning, and retention of lexical collocations in speaking performance.